Mechanism of spillage and excessive boiling of water during vacuum cooling. (August 2015) - Song, Xiao-yan; Liu, Bao-lin; Jaganathan, Ganesh K.; Chen, Lan
Abstract: Immersion vacuum cooling is a novel method for cooling meat products. This method has notable advantages including lower water loss rate of products during the cooling process. However, excessive solution boiling and spillage during immersion vacuum cooling process are considered as the serious problems limiting its wide-spread application. In this study, the mechanism of water boiling and spillage during vacuum cooling was studied by capturing the images of boiling phenomena with a high speed camera. Results show that the growth of bullet bubble is a major reason for more than 42% of water loss during boiling, because the diameter of a bullet bubble can increase to the diameter value of the test tube in 0.36 s. Our results also show that using moderate volumetric displacement of vacuum pump (for instance 0.0012 m 3 s −1 in this paper) and controlling the chamber pressure in the range of 10–2 kPa can weaken the intensity of boiling and spillage of water. These results are discussed in the context of 'classical pool boiling' theory. Highlights: Boiling process of water during vacuum cooling was captured by a high-speed camera. Growth and behavior of bubbles were the major reasons of boiling and spillage. The boiling process consists of boiling flow and slug flow stages. The excessive boiling and spillage mainly appeared at the slug flow stage. An optimal volumetric displacement can weaken the intensity of boiling and spillage.